EDUCATION SYSTEM IN THE USA - G'aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article describes in detail the structure and continuity of the American education system, which is considered advanced today, and the stages of education in a sequence. It describes, among other things, the main functions of pre-school education, secondary education and higher education, as well as information and conclusions about the amount of credit hours allocated to classes and the grading system.